Determinación de la eficacia de la educación en la detección temprana y prevención de complicaciones de pie diabético en el IESS Cotocollao Quito. - Figueroa Saavedra, Irma Augusta (2015)
The diabetic foot is a chronic complication of Diabetes very important from a medical and social perspective, constituting non traumatic most common cause of lower limb amputation, an analytical cross-sectional study was conducted in the outpatient center Cotocollao IESS Quito. The population is made up of a sample of 60 patients attending internal medicine services that were evaluated before and after an educational program for the care of feet in diabetic patients at high risk of complications for the purpose; describe the demographic characteristics of the population at risk of diabetic complications of diabetic foot describe the knowledge, attitudes and practices of self-care of patients at risk of diabetic foot complications establish whether an education program in diabetic patients at risk for complications of diabetic foot improves the level of knowledge, attitudes and self-care practices, the main variables were analyzed; diabetes knowledge, knowledge about foot care, as revised few feet, shoes and appropriate socks, using creams, proper nail trimming, lift the foot, the collected data were entered into Excel and processed with EPI -INFO. Through a survey to determine whether this had a favorable impact on their knowledge, attitudes and self-care practices of which the following main results are obtained 83.3% reported knowing how to care for their feet at the start of the titration and 98.3% (n = 59) it reached the end of it the percentages were higher for both periods and the improvement of knowledge and reached significant difference was observed in general terms that was highly effective in improving knowledge and practices for the care of feet of diabetic patients at high risk KEYWORDS: diabetic foot, educational program, knowledge, attitudes and practices